Research on Internal Audit of Cost and Expense–Take Company C as an example - Yang, Xia (International Journal of Global Economics and Management, 2024)
With the rapid development of market economy, the e-commerce industry and Internet industry have been widely concerned by the society, while the wood processing industry has rarely been concerned by the society. Small and medium-sized wood processing enterprises account for the vast majority of all wood processing enterprises. Studying small and medium-sized wood processing enterprises has important reference for understanding the whole wood processing enterprises. According to the actual development of small and medium-sized enterprises in China, this paper expounds. Taking Company C as an example, this paper adopts the method of literature research, looks at the situation of wood processing industry and the relevant theories of cost and expense internal audit, and refers to the suggestions for solving the problems existing in the cost and expense internal audit of other small and medium-sized enterprises, as well as the relevant theories of enterprise cost and expense internal audit and the production and operation characteristics of Company C, so that theory is linked with practice. This paper probes into the problems in the cost and internal audit of Company C, and gives practical suggestions on the problems in the internal audit of cost and expense, hoping to further reduce the operating cost, reduce the investment loss and improve the profit and technical level of the company.